Application the Single Difference Technique in Aircraft Positioning Using the GLONASS System in the Air Transport - Kamil Krasuski (Communications - Scientific letters of the University of Zilina, 2019)
The article presents the possibility of using the Between Satellite Single Difference method (BSSD) in the precise determination of the aircraft position in the Global Navigation Satellite System GLONASS navigation system. The paper presents the mathematical model of the BSSD method, describes the research test and presents the results of conducted examinations. The research test was conducted within the implementation of the GLONASS satellite technique in air navigation. The test research uses the actual GLONASS navigation data registered by the Topcon HiperPro receiver, mounted onboard a Cessna 172 aircraft. Obtained findings of the research work are interesting from the perspective of implementation of the GLONASS satellite technique in aviation. It should be emphasized that standard deviations of the determined position of the Cessna 172, using the BSSD method, do not exceed 2m. The article also determines the accuracy of a position of the Cessna 172 in the GLONASS solution with reference to a solution in the GPS navigation system.